Pirfenidone suppresses MAPK signalling pathway to reverse epithelial‐mesenchymal transition and renal fibrosis. Issue 8 (6th July 2017) - Li, Zhenzhen; Liu, Xianghua; Wang, Baoying; Nie, Yali; Wen, Jianguo; Wang, Qingwei; Gu, Chaohui
Abstract: Aim: Recent studies indicate that pirfenidone (PFD) may have anti‐fibrotic effects in many tissues, but the potential molecular mechanism remains unknown. The purpose of this study is to investigate the potential effects of PFD on epithelial‐to‐mesenchymal transition (EMT) and renal fibrosis in a unilateral ureteral obstruction (UUO) rat model and the involved molecular mechanism related to cultured human renal proximal tubular epithelial cells (HK‐2). Methods: Sixty rats were randomly divided into three groups: sham‐operated, vehicle‐treated UUO, and PFD‐treated UUO. Kidney specimens were collected at day 7 or 14 after UUO. PFD treatment was also performed for human HK‐2. The tubulointerstitial injury, interstitial collagen deposition, and expression of type I and III collagen, α‐SMA, S100A4, fibronection and E‐cadherin were assessed. In addition, extracellular signal regulated kinase (ERK1/2), p38 MAPK (p38), and c‐Jun N‐terminal kinase/stress‐activated protein kinase (JNK) were also detected. Results: In vitro, PFD significantly attenuated TGF‐β1‐induced EMT and extracellular matrix (ECM) synthesis, as determined by reducing expression of α‐SMA, type I and III collagen, S100A4, fibronection, and increased expression of E‐cadherin. PFD treatment attenuated TGF‐β1‐induced up‐regulation of phosphorylation of ERK1/2, p38 and JNK. In vivo, PFD reduced the degree of tubulointerstitial injury and renal fibrosis, which was associated with reduced expression of TGF‐β1, type III collagen, α‐SMA, S100A4, fibronection, and increased expression of E‐cadherin. Conclusion: These results suggest that pirfenidone is able to attenuate EMT and fibrosis in vivo and in vitro through antagonizing the MAPK pathway, providing a potential treatment to alleviate renal tubulointerstitial fibrosis. Summary at a Glance: This study demonstrated the efficacy of the pirfenidone to improve renal fibrosis in both an experimental rodent model, UUO and on epithelial‐to‐mesenchymal transition and fibrotic markers in cultured human proximal tubular cells. Pirfenidone is an anti‐fibrotic drug used in the treatment of idiopathic pulmonary fibrosis. Hence pirfenidone could be further investigated as a potential treatment to alleviate renal tubulointerstitial fibrosis.